Penerapan Diagnosing Organisasi Melalui Intervensi Technostruktural: Studi Literatur - Marjanis Marjanis; Hendri Yazid; Rasdinal Rasdinal; Nurhizrah Gistituati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Organizational diagnosis is one of the main components in planning change. Organizational diagnosis is fundamental to school development. This can be seen from the organization's diagnosis through technostructural intervention, because it is related to organizational design, employees/employees, and work design. Technostructural intervention method focuses on changes in organizational structure and design, so it tends to be more focused on organizational infrastructure aspects. This method will produce the output of increasing attention to productivity and organizational effectiveness in schools, such as the quality of work culture and methods for designing all components in schools. Schools need to know and strive to meet existing indicators or criteria in order to become a growing organization with high integrity.